THE INTENTION OF FEMALE HIGH SCHOOL STUDENTS TO PREVENT PREMARITAL SEX - Citra Ahiyanasari Ervina Ahiyanasari; Ira Nurmala (Universitas Airlangga, 2017)
Teenagers are susceptible to deviant sexual behavior such as premarital sex behaviors. The number of teens who do premarital sex tend toincrease every year. Premarital sex is at risk of causing unwanted pregnancy and transmission of sexually transmitted diseases. This research aims to understandrelated factors with the intention to prevent premarital sex among female high school students . This is a analytic study used cross sectional design. Sampling was done randomly with a total sample of 75 respondents. Results of this research were analyzed using Gamma correlation test with significance level (α= 0.05). The results of statistical tests indicate that there is a positive relationship between knowledge (p value = 0.007 < α = 0.05) with the intention of preventing premarital sex. Other factors such as the knowledge factors, media usage, attitudes, subjective norms, perceived control is not associated with the intention to prevent premarital sex. The results showed that respondents have a good experience to prevent premarital sex. Efforts to increase knowledge about preventing premarital sex and monitoring the use of media is very necessary for adolescent to have intention to prevent premarital sex. Keyword : premarital sex, high school , prevention